A Menilai Sistem E-learning di Perguruan Tinggi Islam di Jawa Tengah dan Yogyakarta Menggunakan DeLone & McLean dan Model Penerimaan Teknologi - Agus Sutiyono; Syaiful Bakhri; Ulyanti; Dewi Rahayu Ningsih; Fatah Syukur (Jurnal Penelitian Pendidikan IPA, 2024)
This study investigates the effectiveness of e-learning at Islamic universities in Central Java and Yogyakarta using Technology Acceptance Model (TAM) and the DeLone and McLean. It employs variables from both models, including system quality, net benefits, service quality, user satisfaction, perceived ease of use, and intention to use. Data were collected through questionnaires distributed to 250 students from these universities. The research utilizes a quantitative approach and applies proportional random sampling, analyzed with SmartPLS version 3 software. The findings are as follows: (1) Intention to use positively impacts net benefit, with a t-statistic of 1.982 (greater than 1.96) and a p-value of 0.048 (less than 0.05); (2) Perceived ease of use significantly influences intention to use, with a t-statistic of 15.996 (greater than 1.96) and a p-value of 0.000 (less than 0.05); (3) Service quality has a significant effect on user satisfaction, indicated by a t-statistic of 4.221 (greater than 1.96) and a p-value of 0.000 (less than 0.05); (4) System quality also significantly affects user satisfaction, with a t-statistic and p-value of 11.621 which is more than 1.96 and 0.000 which is less than 0.05; (5) Finally, user satisfaction has a significant influence on net benefits, as indicated by a t-statistic and p-value of 14.630 which is more than 1.96 and 0.000 which is less than 0.05.